A physiologically based pharmacokinetic (PBPK) model exploring the blood-milk barrier in lactating species - A case study with oxytetracycline administered to dairy cows and goats. (March 2022) - Tardiveau, Jennifer; LeRoux-Pullen, Lerica; Gehring, Ronette; Touchais, Gaël; Chotard-Soutif, Marie Pierre; Mirfendereski, Hélène; Paraud, Carine; Jacobs, Matthieu; Magnier, Reynald; Laurentie, Michel; Couet, William; Marchand, Sandrine; et al.
Abstract: Antibiotic excretion into milk depends on several factors such as the compound's physicochemical properties, the animal physiology, and the milk composition. The objective of this study was to develop a physiologically based pharmacokinetic (PBPK) model describing the passage of drugs into the milk of lactating species. The udder is described as a permeability limited compartment, divided into vascular, extracellular water (EW), intracellular water (IW) and milk, which was stored in alveolar and cistern compartments. The pH and ionization in each compartment and the binding to IW components and to milk fat, casein, whey protein, calcium, and magnesium were considered. Bidirectional passive diffusion across the blood-milk barrier was implemented, based on in vitro permeability studies. The model application used to predict the distribution of oxytetracycline in cow and goat milk, after different doses and routes of administration, was successful. By integrating inter-individual variability and uncertainty, the model also allowed a suitable estimation of the withdrawal periods. Further work is in progress to evaluate the predictive ability of the PBPK model for compounds with different physico-chemical properties that are potentially actively transported in order to extrapolate the excretion of xenobiotics in milk of various animal species including humans. Graphical abstract: Image 1